Chemical control of field dodder in alfalfa (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Parasitic flowering plants have recently come into focus of research interests as a resultof their notable expansion and increasing damage that they are causing in agriculturalfields. Damage caused by field dodder in alfalfa crops mainly includes reduced yield of fresh biomass and considerable decrease in seed production. Effective control of field dodder in alfalfa crops necessarily includes a number of preventive measures and procedures, as well as chemical control. The effectiveness of glyphosate, propyzamide, imazethapyr and diquat herbicides in controlling field dodder in alfalfa crops was tested in trials conducted in 2011. Pot and field trials were set up in an experimental field of the Institute of Field and Vegetable Crops in Novi Sad (location Rimski Šančevi) and in a private field at Popovići (vicinity of Mladenovac). In pot trials, two glyphosate application rates (288 and 360 g a.i. ha) achieved the highest effectiveness of 95% and 97.5%, respectively. Both application rates of propyzamide (1500 and 2000 g a.i. ha) had weak effectiveness (85% and 87%, respectively), while imazethapyr (150 g a.i. ha) was the weakest herbicide with 80% efficacy. In field trials at both locations, diquat (450 g a.i. ha) showed the best efficacy in controlling field dodder in alfalfa. The efficacy of all other treatments was weaker at Popovići with the following survival rates of field dodder plants: 25% (glyphosate, 288 g a.i. ha), 15% (glyphosate, 360 g a.i. ha), 79%  (propyzamide, 1500 g a.i. ha), 70% (propyzamide, 2000 g a.i. ha) and 72% (imazethapyr,150 g a.i. ha). At the location Rimski Šančevi, the same treatements resulted in around 1% remaining field dodder plants in alfalfa crop.
Keywords: Field dodder; Herbicides; Chemical control; Alfalfa